THROUGH THE LOOKING-GLASS OF THE FAMILIAR: REFRAMING SOVIET AVANT-GARDE CINEMA BETWEEN AESTHETICS AND IDEOLOGY - Malin, Pavel; Changsong, Wang (ASPIRATION Journal, 2025)
This study reinterprets Soviet avant-garde cinema of the 1920s through the analytical lens of Russian Formalism, challenging the prevailing scholarly dichotomy that frames these films either as ideological propaganda or as purely aesthetic experimentation. Employing a formalist conceptual analysis, the study investigates key cinematic devices in selected films by Eisenstein, treating rhythmic, intellectual, metric and tonal montage types as the primary units of analysis. The method integrates formalist principles with sequence analysis to determine how familiar sociopolitical motifs function within the perceptual logic of poetic cinema. The findings reveal that revolutionary and socialist imagery in avant-garde films operates not as direct ideological messaging but as perceptually automatized material necessary for generating defamiliarization effects. Devices such as rhythmic, intellectual, metric and tonal montage reconfigure these familiar motifs into sites of renewed perception, confirming their role as formal prerequisites rather than propagandistic ends. The analysis further shows that the historical displacement of Formalism by Marxist and post-structuralist frameworks shaped later misreadings of Soviet cinema, obscuring its original system-bound aesthetic rationale. It concludes that Soviet avant-garde cinema’s political motifs should be understood as integral components of a wider formal system grounded in perceptual estrangement. This approach provides a historically informed analytical model for reassessing early Soviet film beyond ideological binaries and offers a foundation for further research on how aesthetic systems emerge from and respond to their cultural zeitgeist.